Um olhar bakhtiniano sobre as narrativas áridas de Vidas Secas, de Graciliano Ramos, e Os Flagelados do Vento Leste, de Manuel Lopes - Araújo, Adriana Garcia (2021)
This work aims to make a comparative study between two novels Portuguese: Barron Lives, originally entitled Vidas Secas (1976), by Graciliano Ramos, and Os Flagelados do Vento Leste (1979), by Manuel Lopes, which first is part of Brazilian Literature and the second is part of Cape Verdean Literature. The spread of the authors inside the modernist movements in their respective countries (Brazil and Cape Green, respectively) were considered, due to the importance of the works for the raising of a national identity and the social criticism that they make up in refracting the real historical conditions. While checking the state of the art, it was verified a small number of works that approached the same corpus within the perspective proposed here, anchored in the studies of Bakhtin and the Circle, especially in the work A Teoria do Romance, by Mikhail M. Bakhtin. Therefore, this research is relevant to the studies involving Portuguese-speaking African literature and Brazilian literature, since adds a new possibility of reading the works and because it collaborates with the strengthening of AfroLusophone literature studies. The choices by the Bakhtinian theory and the methodological path adopted are justified by Theory of Literature, Criticism, and literary history, considering the linguistic and extralinguistic aspects of the works. In both novels is possible to notice that the characters act in different ways, even they are in similar conditions, what leads us to presume that the actions are not guided only by social determinism, but also by subjective aspects, leading us to ask: what are the main elements that design characters' personality and how does it affect their positions, marked in their actions in the represented world? The research confirms the well-built literary dialogism that exists between the two countries and the importance of the authors and their works in the social and political context in which they are settled in, refracting these moments in the weaving of their novels. Through the different types of discourses overlapped in the voices that permeate the narrative, we unveil the social voices that constitute and question the actions of the characters. Moreover, in the chronotopes analysis, it was verified that human/nature relationship happens in different ways in each novel, and this relation constitute the characters. Those aspects confirm previous presumptions that the characters do not act guided only by social determinism, but also by their subjectivities. In this way, research results mark that characters' ideological constitution happens in the tension between different discourses that unveil the social voices that challenge them, as well as in the space-time in which they live and which interferes in their action. The junction of these factors designs characters' subjectivity, leading their behaviors, thus building an individual conscience that affects their relations in society, solidifying or not a collective behavior.